Empowering The Mind: Intervensi One-Day Positive Self-Talk untuk Menurunkan Tingkat Kecemasan pada Ibu Hamil - Aeni, Nurul; Anita, Nur; Diana, St. Aras (Mando Care Jurnal, 2025)
This study aims to determine the effectiveness of the One-Day Positive Self-Talk Session in reducing anxiety levels among pregnant women. Anxiety during pregnancy is a common condition that can negatively impact the physical and psychological health of the mother as well as the development of the fetus. This research uses a quasi-experimental design with a one-group pretest-posttest approach. Participants in this study were 20 pregnant women in their second and third trimesters who attended a one-day positive self-talk training session. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. Data analysis using the paired sample t-test revealed a statistically significant reduction in anxiety levels after attending the training session (p<0.05). The findings of this study indicate that the One-Day Positive Self-Talk Session is effective in reducing anxiety among pregnant women. The implications of this study support the use of brief and practical interventions such as positive self-talk as part of psychological support programs for pregnant women in primary healthcare services and communities.